Review of the enigmatic ‘shark’, Platyacrodus unicus Ameghino, 1935, from the Paleocene of Patagonia, Argentina: a history of palaeontologists, sharks and crabs - Bogan, Sergio; Agnolin, Federico; Ezcurra, Martín D. (Zootaxa, 2019)
Platyacrodus unicus Ameghino, 1935, was described as an enigmatic shark probably related to the clade Heterodontidae. This species was described based on a single, small crushing tooth-like element coming from the “Salamancan” (Danian) of the Western Río Chico locality, Chubut province, Patagonia, Argentina. The holotype and only known specimen was never figured and only briefly characterized by its original describer Florentino Ameghino. The finding of the original figures and holotype specimen allows for a re-evaluation of the taxonomic status of this species. Here, Platyacrodus unicus is reinterpreted as the carapace of a small retroplumid crab of the genus Costacopluma Collins & Morris, 1975.